2019
DOI: 10.1128/aac.00838-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gradient Concentration Strip Method for Antifungal Susceptibility Testing of Isavuconazole and Comparators for Mucorales Species

Abstract: MIC values for amphotericin B and three azoles determined by the EUCAST reference technique and by gradient concentration strips were compared for 30 Mucorales isolates belonging to clinically important species. Essential agreement (EA) within ±2 dilution steps at 24 hours between the techniques was 83.3% for isavuconazole. EAs for itraconazole, amphotericin B, and posaconazole were 86.7%, 73.3%, and 56.7%, respectively. A good agreement was obtained between visual and spectrophotometric readings for EUCAST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous reports had some reservations about the Etest method due to a low level of agreement between reference methods and Etest [ 24 , 25 ]. Of note, a recent study by Vidal et al described a good correlation between these methods [23] . Though not optimal, Etest can be utilized for antifungals susceptibility testing in Mucorales.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous reports had some reservations about the Etest method due to a low level of agreement between reference methods and Etest [ 24 , 25 ]. Of note, a recent study by Vidal et al described a good correlation between these methods [23] . Though not optimal, Etest can be utilized for antifungals susceptibility testing in Mucorales.…”
Section: Methodsmentioning
confidence: 91%
“…Antimicrobial susceptibility testing and MIC (minimum inhibitory concentration) determination are vital for managing invasive mucormycosis. The recommended reference technique for antifungals susceptibility is the broth microdilution method by the Clinical Laboratory Standards Institute (CLSI) or the (European Committee on Antimicrobial Susceptibility Testing) EUCAST [23] . Gradient concentration strip test (Etest) is now getting recognition as a quick and easy method to determine the antifungals susceptibility [23] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presents the first in vitro evidence of the effects of the association of two antifungals against Mucorales, evaluated by the Gradient Concentration Strip Method. Even if deviates from the standard microdilution checkerboard methodology, P Vidal et al reported that the essential agreement within ±2 dilution steps at 24 hours between these techniques was 83.3% and 73.3% for ISA and AMB, respectively [ 25 , 26 ]. However, ETSM can help the clinical management of mucoromycosis from a practical point of view, due to its feasibility in the laboratory, adapting the technical procedure proposed by A Espinel-Ingroff et al for Mucorales [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disc diffusion appears feasible, with a low rate of major and very major errors demonstrated for posaconazole and amphotericin B when using cutoffs of 1 and 4 mg/L to pragmatically define sensitivity and resistance, respectively [ 207 ]. There have been conflicting studies with gradient strip testing, with some studies showing reasonable agreement of MICs and others demonstrating conflicting results, especially for amphotericin B and posaconazole [ 197 , 217 , 218 , 219 ].…”
Section: Diagnosticsmentioning
confidence: 99%